Contacting metallic nanoparticles on transparent substrates. Issue 7 (24th June 2013) - Erbe, A.; Wiesenhütter, U.; Grebing, J.; Fassbender, J.
<x xml:space="preserve">Abstract</x> We demonstrate reliable contacting of metallic nanoparticles in metallic junctions. The junctions are prepared using electron beam lithography (EBL) and investigated by means of transmission electron microscopy (TEM) and electrical transport measurements. The size, shape, and crystalline structure of the particles can be clearly identified in our junctions. These properties are then related to low temperature measurements of the conductance of these devices. Due to the weak coupling of the metallic electrodes to the particles, Coulomb blockade (CB) effects are found in these junctions. <inline-graphic xlink:href="ark:/27927/pgg277v2hds" content-type="pssa201228769-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Au nanoparticles situated in between Au nanocontacts imaged in a transmission electron microscope.